2006
DOI: 10.5089/9781451865608.001
|View full text |Cite
|
Sign up to set email alerts
|

A VAR Analysis of Kenya's Monetary Policy Transmission Mechanism: How Does the Central Bank's REPO Rate Affect the Economy?

Abstract: This Working Paper should not be reported as representing the views of the IMF.The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit comments and to further debate. This paper examines the impact of a monetary policy shock on output, prices, and the nominal effective exchange rate for Kenya using data during 1997-2005. Based on techniques comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 10 publications
5
32
0
Order By: Relevance
“…The first two equations suggest that output and consumer prices are sluggish in responding to shocks to monetary variables in the economy. This scheme is based on the observation that most types of real economic activity may respond only with a lag to monetary variables because of inherent inertia and planning delays (Bernanke and Mihov, 1997; Karame and Olmedo, 2002; Becklemans, 2005; Vonnak, 2005; Cheng, 2006).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first two equations suggest that output and consumer prices are sluggish in responding to shocks to monetary variables in the economy. This scheme is based on the observation that most types of real economic activity may respond only with a lag to monetary variables because of inherent inertia and planning delays (Bernanke and Mihov, 1997; Karame and Olmedo, 2002; Becklemans, 2005; Vonnak, 2005; Cheng, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Becklemans (2005) uses a real trade‐weighted exchange rate index in a study of Australia and assumes that the index responds instantaneously to all variables in the system. In a study of Kenya, Cheng (2006) employs a nominal effective exchange rate and maintains that the exchange rate responds contemporaneously to all variables in the SVAR. Similarly, Borys and Hovarth (2007) in a study of the Czech Republic and Piffanelli (2001) in a study of Germany assume all variables in the system affect exchange rates instantaneously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Kenya, which maintained a managed float during the sample period, Cheng (2006) used VAR techniques to find that policy-driven interest rates had a considerable impact on the foreign exchange value of the shilling. He found that the exchange rate channel accounted for about one-fourth of the variation in inflation, but suggested that the effect operated mostly through pass-through rather than expenditure-switching effects, since he found much weaker effects on real aggregate demand and economic activity.…”
Section: The Exchange Rate Channelmentioning
confidence: 99%
“…Thus, the relationship between the reduced form errors and the disturbances become lower triangular. As in Cheng (2006), a non-fuel world commodity price index (Comm) and a world fuel price index (Oil) are used as exogenous variables to control for external shocks in the constant parameter VAR estimation. A wage index (wages) is also used to capture the impact of externally driven supply side factors that have driven structural breaks in South Africa over the sample period.…”
Section: Resultsmentioning
confidence: 99%